A study of feto-maternal outcome in cases of pre-labour rupture of membranes - U. T., Koothan; Kate, Nina V.; V., Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prelabour rupture of membranes is a common obstetric problem and the assessment of women with possible membrane rupture is a management issue faced in every day practice. The diagnosis and treatment of Prelabour rupture of membranes depends upon the facilities available. Unrecognized and inadequately treated conditions can lead to various maternal and neonatal complications. Methods: The present prospective study was conducted on 200 pregnant women satisfying the inclusion criteria after getting consent for participation. Pregnant women between the gestational age of 28 – 40 weeks who presented with Prelabour rupture of membranes to casualty were enrolled into the study. Results: 76.5% of the study participants were between 37-40 weeks of gestation and the remaining 23.5% belonged to the preterm population. Maternal morbidity was found to be 68% among the study participants with latency period more than 24 hrs. 37.5% of the neonates developed morbidity and the neonatal mortality was 2%. Conclusions: Prelabour rupture of membranes contributes significantly to maternal morbidity, neonatal morbidity and perinatal mortality.